Synthesis and Characterisation of Carbon Nanomaterial on Short Carbon Fiber by Fluidized Bed Chemical Vapour Deposition and Fabrication of Carbon Nanocomposite - Vishkaei, Mahta Sadegh (2009)
Although there are some researches on the whiskerization of CNPs on carbon fiber, but none has studied it in the fluidized bed. This research has carried out to study the whiskerization of carbon nanoparticles on short carbon fiber by fluidized bed reactor chemical vapour deposition (FBCVD). The CNP whiskerized CF was added by appropriate amount of Polypropylene to make a composite. Some information about catalyst, nanostructural features of nanoparticles and composite discussed. Hence, in this work, experimental studies were carried out to elucidate the influential parameters and investigate the influence of (i) synthesis temperature, (ii) catalyst type (iii) carbon source gas flow rate on CNP quality in FBCVD process. The synthesis of carbon nanoparticles (CNPs) have been done by the catalytic decomposition of acetylene over Fe/CF catalysts in a fluidized bed reactor. The general growing conditions were: 40 L/min flow rate, 450-650°C synthesis temperature, atmospheric pressure and three gas compositions: 50% , 25% and 25% C2H2/H2/N2. The catalyst substrate was carbon fiber with different sizes (1mm and 2mm) and metal catalyst with different content of iron (0.23%, 1.8% and 4.92%) were used to deposit on the CF surface. Characterization of the catalysts and the products was performed by X ray diffraction patterns (XRD), scanning electron microscope (SEM) and thermal gravimetric analysis (TGA). An apparent relationship was found to exist between the metallic iron content of the catalysts, substrate size, and the final characteristics of the carbon products. Then the composite was prepared with the best percentage of whiskerized carbon fiber and polypropylene with concentration of 2% and 98% respectively. The mixture introduced into the mixer (The rotor speed and temperature were set at 120 rpm and 180oC, and mixing continued for 10 min). Finally the composite was analyzed by Dynamic Mechanical Analysis (DMA) for mechanical properties. This study indicates that the optimum condition for the growth of CNP on CF is 600 °C for 1.8% Fe on carbon fiber with 2mm length for a 30 minutes deposition time and 15L/min acetylene flow rate.